Mosquito repelling bracelet containing N, N-diethyl-2-hydroxy-2-phenylacetamide

By using components such as N,N-diethyl-2-hydroxy-2-phenylacetamide and PLGA in mosquito repellent bracelets, the problems of short-term mosquito repellent effect and insufficient mechanical properties of traditional mosquito repellent bracelets are solved, and a durable, stable and durable mosquito repellent effect is achieved.

CN119908369APending Publication Date: 2025-05-02BEIJING SIRUILANGWEN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101814.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The traditional mosquito repellent bracelet has a short duration of mosquito repellent effect, making it difficult to play a stable role under different environmental conditions, and has insufficient mechanical properties and is prone to damage.

Method used

The mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide is used to regulate the release rate of mosquito repellent components and enhance mechanical properties by combining with the polymer carrier PLGA with sustained release function, the plasticizer tributyl citrate, the antioxidant BHT, the fragrance lavender essential oil, nanotitanium dioxide and the degradable thermoplastic polyurethane elastomer.

Benefits of technology

It achieves the durability and stability of the mosquito repellent effect, can continue to play the role of mosquito repellent within 7-10 days, and maintains stable performance under different environmental conditions, while improving the mechanical properties and durability of the bracelet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254386110000121
    Figure BDA0005254386110000121
  • Figure BDA0005254386110000131
    Figure BDA0005254386110000131
Patent Text Reader

Abstract

The invention belongs to the field of material chemical industry, discloses a mosquito repelling bracelet containing N, N-diethyl-2-hydroxy-2-phenylacetamide and a preparation method of the mosquito repelling bracelet, and particularly relates to the mosquito repelling bracelet containing the N, N-diethyl-2-hydroxy-2-phenylacetamide. The bracelet comprises the following components in parts by mass: 3-10 parts of a mosquito-repelling component, 8-15 parts of a polylactic acid-glycollic acid copolymer carrier, 2-6 parts of a tributyl citrate plasticizer and the like, and a modified organic compound can be added to improve the performance. The preparation method comprises a plurality of steps, such as preparation of PLGA microspheres loaded with mosquito repellent components and the like. A contrast test shows that the bracelet disclosed by the invention is excellent in mosquito repelling performance, antibacterial performance, ultraviolet resistance and the like, high in residual quantity of N, N-diethyl-2-hydroxy-2-phenylacetamide, excellent in slow release and good in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical materials, and in particular to a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide. Background Art

[0002] At a time when people's requirements for quality of life are constantly improving, wearable products with special functions are increasingly attracting attention. As a product that can provide people with convenient mosquito protection during outdoor activities, the performance of mosquito repellent bracelets is crucial. Traditional commercially available ordinary mosquito repellent bracelets that use natural plant essential oils to repel mosquitoes have many disadvantages. On the one hand, its mosquito repellent effect lasts for a short time, and the effect usually decreases significantly after 3 days of use, which cannot meet people's needs for long-term outdoor activities. On the other hand, under different environmental conditions, such as changes in humidity, temperature, and light, its mosquito repellent performance fluctuates greatly and it is difficult to play a stable role. Moreover, the mechanical properties of this type of bracelet are poor, the tensile strength and elongation at break are limited, and it is easy to be damaged during daily wear. Therefore, it is urgent to develop a new type of mosquito repellent bracelet with a long-lasting mosquito repellent effect, adaptability to various environments, and good mechanical properties. Summary of the invention

[0003] The present invention provides a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide, which comprises, by weight:

[0004] 3-10 parts of N,N-diethyl-2-hydroxy-2-phenylacetamide;

[0005] 8-15 parts of a high molecular polymer carrier with sustained release function, the carrier is polylactic acid-glycolic acid copolymer (PLGA), the molar ratio of lactic acid to glycolic acid is 75:25-50:50, and the molecular weight is 50000-100000;

[0006] 2-6 parts of plasticizer, tributyl citrate;

[0007] 1-4 parts of antioxidant, which is butylated tert-cresol (BHT);

[0008] 0.5-2 parts of spices, such as lavender essential oil;

[0009] 0.1-1 part of nano titanium dioxide, with a particle size of 20-50 nanometers;

[0010] The balance is a degradable elastic material, such as thermoplastic polyurethane elastomer (TPU), and the elastic material contains 10-20% by mass of nanocellulose to enhance the mechanical properties and stability of the bracelet.

[0011] Furthermore, in the mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide, the high molecular polymer carrier PLGA with sustained release function regulates the release rate of N,N-diethyl-2-hydroxy-2-phenylacetamide by changing the ratio of lactic acid to glycolic acid and the molecular weight.

[0012] Furthermore, in the mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide, the nano titanium dioxide not only has an antibacterial effect to prevent bacteria from growing on the surface of the bracelet, but also can promote the photodegradation of N,N-diethyl-2-hydroxy-2-phenylacetamide under ultraviolet irradiation, so that it slowly releases active ingredients, further enhancing the mosquito repellent effect.

[0013] Further, a method for preparing a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide comprises the following steps:

[0014] Preparation of PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide: dissolving N,N-diethyl-2-hydroxy-2-phenylacetamide in dichloromethane, adding the dichloromethane solution of PLGA, and ultrasonic emulsification to form an oil phase; slowly dropping the oil phase into an aqueous solution containing polyvinyl alcohol (PVA), stirring at a high speed to volatilize the dichloromethane, and forming PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide;

[0015] Prepare a mixed solution: add plasticizer tributyl citrate, antioxidant di-tert-butyl-p-cresol (BHT), fragrance lavender essential oil, and nano titanium dioxide into an appropriate amount of tetrahydrofuran (THF), stir evenly, and form a mixed solution;

[0016] Preparation of mosquito repellent bracelet material: adding PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide to the above mixed solution, and then adding thermoplastic polyurethane elastomer (TPU) containing nanocellulose, stirring at 50-70° C. until completely dissolved to form a uniform solution;

[0017] Molding: Pour the above solution into a customized bracelet mold, cool it naturally at room temperature to form it, or dry it at 40-60°C to form it, and after demolding, a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide is obtained.

[0018] Furthermore, in the process of preparing PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide, the particle size distribution and encapsulation efficiency of the microspheres were adjusted by changing the power and time of ultrasonic emulsification and the concentration of PVA.

[0019] Furthermore, in the molding step, when a hot pressing molding process is adopted, the pressure is controlled at 5-10 MPa, the temperature is 120-150° C., and the time is 5-10 minutes.

[0020] Furthermore, the mosquito repellent bracelet is used in outdoor activities. The mosquito repellent bracelet can effectively repel mosquitoes in outdoor activities such as camping, hiking, fishing and the like, providing users with continuous mosquito repellent protection for up to 7-10 days, and can maintain a stable mosquito repellent effect under different ambient temperature (15-35°C) and humidity (40-80%) conditions.

[0021] Furthermore, the prepared mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide is characterized in that the bracelet has good flexibility and wearing comfort, its tensile strength reaches 10-15MPa, and its elongation at break is 300-500%. It can adapt to the wearing requirements of different wrist sizes and is not easy to deform or damage during long-term use.

[0022] A modified organic compound is further added, and the modified organic compound is one or more of 3-amino-4-methoxyphenylacetic acid benzyl ester, 2-hydroxy-5-nitrobenzaldehyde semicarbazone, 4-chloro-3-methylbenzoic acid-2-methoxyethyl ester, 5-bromo-2-hydroxyacetophenone oxime, 3-mercapto-5-methoxybenzoic acid butyl ester, 4-amino-3-chlorobenzoic acid isopentyl ester, and 2-hydroxy-4-nitrobenzoic acid hydrazide.

[0023] Furthermore, in the step of preparing the mixed solution, a modified organic compound in corresponding parts by weight is added, and the weight of the modified organic compound is adjusted according to actual needs while ensuring the stability of the overall formula.

[0024] Beneficial technical effects:

[0025] Excellent mosquito repellent effect: Compared with ordinary mosquito repellent bracelets on the market, the mosquito repellent effect of homemade bracelets is greatly extended, and can be used for 7 days or more to effectively repel mosquitoes. In complex outdoor environments such as different humidity, temperature, and light, by adding specific modified organic compounds, the stability of the mosquito repellent effect can be specifically improved. For example, the mosquito repellent effect can still reach 80% after 8 days of use in a high temperature environment.

[0026] Excellent mechanical properties: tensile strength can reach 11-14MPa, elongation at break is 350%-450%, which is significantly better than ordinary bracelets. It can adapt to different wearing scenarios and is not easy to deform or damage after long-term use, ensuring the durability of the product.

[0027] Stable residual ingredients: In scenarios such as simulated sweating and daily wear friction, the bracelet with modified organic compounds has a higher residual amount of N,N-diethyl-2-hydroxy-2-phenylacetamide, which can still maintain a high proportion after several days of use, ensuring the continued effect of the active ingredients and maintaining stable mosquito repellent performance.

[0028] Enhanced antibacterial performance: After adding nano-titanium dioxide, the growth of bacteria on the surface of the bracelet is effectively inhibited, providing users with a healthier wearing experience and broadening the application advantages of the product. DETAILED DESCRIPTION

[0029] Example 1

[0030] Preparation of PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide:

[0031] 5 g of N,N-diethyl-2-hydroxy-2-phenylacetamide was dissolved in 50 ml of dichloromethane, and a dichloromethane solution of 10 g of PLGA (molar ratio of lactic acid to glycolic acid was 75:25, molecular weight was 80,000) was added, and ultrasonic emulsification (power 300 W, time 20 min) was performed to form an oil phase.

[0032] The oil phase was slowly added dropwise to a 200 ml aqueous solution containing 2% polyvinyl alcohol (PVA), and stirred at high speed (1000 rpm) to evaporate the dichloromethane to form PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide. Microscopic observation showed that the particle size of the microspheres was between 80 and 150 μm.

[0033] Preparation of mixed solution:

[0034] 3 g of tributyl citrate, 2 g of di-tert-butyl-p-cresol (BHT), 1 g of lavender essential oil, and 0.5 g of nano-titanium dioxide (particle size 30 nm) were added to 100 ml of tetrahydrofuran (THF), and stirred evenly to form a mixed solution.

[0035] Materials for making mosquito repellent bracelet:

[0036] PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide were added to the above mixed solution, and then 20 g of thermoplastic polyurethane elastomer (TPU) containing 15% nanocellulose was added, and stirred at 60° C. until completely dissolved to form a uniform solution.

[0037] forming:

[0038] The above solution was poured into a customized bracelet mold, naturally cooled and formed at room temperature, and a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide was obtained after demolding.

[0039] Comparative test:

[0040] Take the same specifications of the commercially available common mosquito repellent bracelet (using natural plant essential oil to repel mosquitoes) and the mosquito repellent bracelet prepared in this embodiment, and test the mosquito repellent effect in the same outdoor environment (temperature 25°C, humidity 60%). The results show that the mosquito repellent effect of the commercially available common mosquito repellent bracelet has significantly decreased after 3 days of use, and the number of mosquito bites has increased significantly; while the mosquito repellent bracelet prepared in this embodiment can still effectively repel mosquitoes after 7 days of use, and the number of mosquito bites is less. At the same time, the two bracelets were subjected to a tensile test. The tensile strength of the commercially available common bracelet is 8MPa, and the elongation at break is 250%; the tensile strength of the bracelet of this embodiment reaches 12MPa, and the elongation at break is 400%, indicating that the bracelet of this embodiment has better mechanical properties and durability.

[0041] Example 2

[0042] Preparation of PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide:

[0043] 7 g of N,N-diethyl-2-hydroxy-2-phenylacetamide was dissolved in 60 ml of dichloromethane, and a dichloromethane solution of 12 g of PLGA (molar ratio of lactic acid to glycolic acid was 60:40, molecular weight was 60,000) was added, and ultrasonic emulsification (power 250 W, time 15 min) was performed to form an oil phase.

[0044] The oil phase was slowly added dropwise to 250 ml of aqueous solution containing 1.5% polyvinyl alcohol (PVA), and stirred at high speed (1200 rpm) to volatilize the dichloromethane to form PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide. The particle size of the microspheres was found to be between 60 and 120 μm.

[0045] Preparation of mixed solution:

[0046] 4 g of tributyl citrate, 2.5 g of di-tert-butyl-p-cresol (BHT), 1.5 g of lavender essential oil, and 0.8 g of nano-titanium dioxide (particle size 40 nm) were added to 120 ml of tetrahydrofuran (THF), and stirred evenly to form a mixed solution.

[0047] Materials for making mosquito repellent bracelet:

[0048] PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide were added to the above mixed solution, and then 25 g of thermoplastic polyurethane elastomer (TPU) containing 18% nanocellulose was added, and stirred at 55° C. until completely dissolved to form a uniform solution.

[0049] forming:

[0050] The above solution was poured into a customized bracelet mold, dried at 45°C to form, and after demolding, a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide was obtained.

[0051] Comparative test:

[0052] Under simulated humidity environments (humidity 40%, 60%, 80%), the mosquito repellent effect of the mosquito repellent bracelet prepared in this embodiment and another bracelet of the same model without nano-titanium dioxide was tested. The results show that at a humidity of 40%, the mosquito repellent effect of the two bracelets is similar; but at a humidity of 60% and 80%, the mosquito repellent effect of the bracelet without nano-titanium dioxide decreases rapidly over time, while the mosquito repellent effect of the bracelet in this embodiment remains relatively stable due to the photodegradation promotion effect of nano-titanium dioxide. At the same time, the two bracelets were tested for antibacterial effects. Under the same bacterial culture environment, the amount of bacteria growing on the surface of the bracelet in this embodiment is significantly less than that of the bracelet without nano-titanium dioxide, indicating that the addition of nano-titanium dioxide effectively enhances the antibacterial properties of the bracelet.

[0053] Example 3

[0054] Preparation of PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide:

[0055] 4 g of N,N-diethyl-2-hydroxy-2-phenylacetamide was dissolved in 40 ml of dichloromethane, and 8 g of PLGA (molar ratio of lactic acid to glycolic acid was 50:50, molecular weight was 100000) in dichloromethane solution was added, and ultrasonic emulsification (power 350 W, time 25 min) was performed to form an oil phase.

[0056] The oil phase was slowly added dropwise to 180 ml of aqueous solution containing 2.5% polyvinyl alcohol (PVA), and stirred at high speed (800 rpm) to volatilize the dichloromethane to form PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide, with a particle size of 100-180 μm.

[0057] Preparation of mixed solution:

[0058] 2.5 g of tributyl citrate, 1.5 g of di-tert-butyl-p-cresol (BHT), 0.8 g of lavender essential oil, and 0.6 g of nano-titanium dioxide (particle size 25 nm) were added to 80 ml of tetrahydrofuran (THF), and stirred to form a mixed solution.

[0059] Materials for making mosquito repellent bracelet:

[0060] PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide were added to the above mixed solution, and then 18 g of thermoplastic polyurethane elastomer (TPU) containing 12% nanocellulose was added, and stirred at 65° C. until completely dissolved to form a uniform solution.

[0061] forming:

[0062] The above solution was poured into a customized bracelet mold, and a hot pressing molding process was adopted. The pressure was controlled at 8 MPa, the temperature was 130°C, and the time was 8 minutes. After demolding, a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide was obtained.

[0063] Comparative test:

[0064] The performance of the wristband prepared by the hot pressing molding process and the same wristband prepared by the natural cooling molding process in this embodiment is compared. The surface of the hot pressing molded wristband is smoother, the molding precision is higher, the tensile strength reaches 14MPa, and the elongation at break is 450%; the tensile strength of the naturally cooled molded wristband is 11MPa, and the elongation at break is 350%. In terms of mosquito repellent effect, the two wristbands have similar effects when used in the same environment, but the hot pressing molded wristband has a denser structure and a more stable sustained release effect of the mosquito repellent ingredients during long-term use. After 8 days of use, it can still maintain a good mosquito repellent effect.

[0065] Example 4

[0066] Modified organic compound: 3-amino-4-methoxyphenylacetic acid benzyl ester

[0067] Design principle: The amino group can react with the carboxyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form a stable amide bond, achieving covalent connection between the two and improving the load stability. The methoxy group enhances the hydrophilicity of the molecule, making it better dispersed in the system. The benzyl group of the benzyl phenylacetate part has a certain hydrophobicity and can combine with fibers and other organic components through hydrophobic effects. The ester group can be hydrolyzed under different environments, providing a controllable pathway for the sustained release of N,N-diethyl-2-hydroxy-2-phenylacetamide.

[0068] Mechanism of group action: The amino group reacts with the carboxyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form a stable chemical bond, ensuring that N,N-diethyl-2-hydroxy-2-phenylacetamide is firmly connected to the modified compound. The methoxy group improves the solubility of the molecule in the finishing agent and makes it evenly dispersed. The ester group will slowly hydrolyze under the action of moisture or microorganisms, gradually cutting off the connection with N,N-diethyl-2-hydroxy-2-phenylacetamide to achieve sustained release. The benzyl group interacts with the polymer material of the bracelet to enhance adhesion.

[0069] Synthesis method: 3-amino-4-methoxyphenylacetic acid and benzyl alcohol are used as raw materials, and esterification reaction is carried out in toluene solvent under heating and reflux under concentrated sulfuric acid catalysis. After the reaction is completed, the reaction solution is poured into a saturated sodium carbonate solution, separated, and the organic phase is taken, dried with anhydrous sodium sulfate, filtered, and toluene is removed by reduced pressure distillation to obtain 3-amino-4-methoxyphenylacetic acid benzyl ester.

[0070] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing the mixed solution of the mosquito repellent bracelet, 5 parts of 3-amino-4-methoxyphenylacetic acid benzyl ester were added. The other steps were the same as those in Example 1.

[0071] Comparative test: The mosquito repellent bracelet prepared in this embodiment is compared with the bracelet without the modifier added in Example 1. Tested in an outdoor high temperature (35°C) environment, the mosquito repellent effect of the bracelet in this embodiment can still reach 80% after 8 days of use, while the mosquito repellent effect of the bracelet in Example 1 is reduced to 60%.

[0072] Example 5

[0073] Modified organic compound: 2-Hydroxy-5-nitrobenzaldehyde semicarbazone

[0074] Design principle: The hydroxyl group can form hydrogen bonds with the hydroxyl group in the bracelet material to enhance adhesion. The imine group after condensation of the aldehyde group undergoes a nucleophilic addition reaction with the carbonyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to achieve loading. The nitro group has strong electron-withdrawing properties and can adjust the electron cloud distribution of the molecule, affecting the interaction with N,N-diethyl-2-hydroxy-2-phenylacetamide and the adsorption performance in the bracelet. The semicarbazide part can interact weakly with other additives to stabilize the system.

[0075] Mechanism of group action: The hydroxyl group forms a hydrogen bond with the hydroxyl group of the bracelet material and is tightly bound. The imine group reacts with the carbonyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form a stable connection. The nitro group changes the surrounding electron cloud through the electron-withdrawing effect, making the binding of N,N-diethyl-2-hydroxy-2-phenylacetamide more stable. Under different humidity environments, the interaction between aminourea and water molecules can adjust the conformation of the modified compound, thereby affecting the release of N,N-diethyl-2-hydroxy-2-phenylacetamide.

[0076] Synthesis method: 2-hydroxy-5-nitrobenzaldehyde and semicarbazide are added to an ethanol solution in a certain proportion and stirred at room temperature for reaction. After the reaction is completed, ethanol is removed by vacuum distillation to obtain a crude product, which is then recrystallized using a mixed solvent of ethanol and water to obtain pure 2-hydroxy-5-nitrobenzaldehyde semicarbazide.

[0077] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing the mixed solution of the mosquito repellent bracelet, 4 parts of 2-hydroxy-5-nitrobenzaldehyde semicarbazone were added. The other steps were the same as those in Example 2.

[0078] Comparative test: The mosquito repellent bracelet prepared in this embodiment is compared with the common mosquito repellent bracelet on the market. In a high humidity (80%) environment, the mosquito repellent rate of the bracelet in this embodiment is still as high as 75% after 6 days of use, while the repellent rate of the common bracelet on the market is only 40%.

[0079] Example 6

[0080] Modified organic compound: 2-methoxyethyl 4-chloro-3-methylbenzoate

[0081] Design principle: Chlorine atoms can undergo substitution reaction with the hydroxyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to achieve loading. The methyl group adjusts the spatial structure and hydrophobicity of the molecule, allowing it to better combine with the bracelet material. The ester group of benzoic acid-2-methoxyethyl ester can be hydrolyzed under different environments to control the release of N,N-diethyl-2-hydroxy-2-phenylacetamide. The methoxy group enhances the hydrophilicity of the molecule and improves its dispersibility in the system.

[0082] Mechanism of group action: Chlorine atoms react with the hydroxyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form a stable ether bond. The methyl group affects the interaction of the molecule with other components through steric hindrance and electronic effects. The ester group hydrolyzes under acidic or alkaline conditions and gradually releases N,N-diethyl-2-hydroxy-2-phenylacetamide. The methoxy group makes the molecule soluble in water and easier to disperse evenly during the preparation process.

[0083] Synthesis method: 4-chloro-3-methylbenzoic acid and 2-methoxyethanol are used as raw materials, and the esterification reaction is carried out by heating and refluxing in cyclohexane solvent under the catalysis of concentrated sulfuric acid. After the reaction is completed, it is washed with saturated sodium bicarbonate solution and water in turn, separated, and the organic phase is taken, dried with anhydrous sodium sulfate, filtered, and then distilled under reduced pressure to remove cyclohexane to obtain 4-chloro-3-methylbenzoic acid-2-methoxyethyl ester.

[0084] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing the mixed solution of the mosquito repellent bracelet, 6 parts of 4-chloro-3-methylbenzoic acid-2-methoxyethyl ester were added. The other steps were the same as those in Example 3.

[0085] Comparative test: The mosquito repellent bracelet prepared in this embodiment was compared with the same bracelet without adding the modifier. In a simulated sweating environment, after the bracelet of this embodiment was used for 5 days, the residual amount of N,N-diethyl-2-hydroxy-2-phenylacetamide was 60% of the initial loading amount, while the residual amount of the bracelet without adding the modifier was only 40%.

[0086] Example 7

[0087] Modified organic compound: 5-bromo-2-hydroxyacetophenone oxime

[0088] Design principle: The hydroxyl groups form hydrogen bonds with the hydroxyl groups on the surface of the bracelet material to enhance adhesion. The oxime groups form hydrogen bonds or other weak interactions with N,N-diethyl-2-hydroxy-2-phenylacetamide to achieve loading. Bromine atoms increase the stability and steric hindrance of the molecules, regulate the existence state of the molecules in the bracelet and the interaction with other components, thereby affecting the release of N,N-diethyl-2-hydroxy-2-phenylacetamide.

[0089] Mechanism of group action: The hydroxyl group is closely connected to the hydroxyl group of the bracelet material through hydrogen bonds. The oxime group is combined with N,N-diethyl-2-hydroxy-2-phenylacetamide through hydrogen bonds or van der Waals forces to stabilize the load. The large atomic radius and strong electronegativity of the bromine atom change the electron cloud distribution and spatial structure of the molecule, affecting the interaction between molecules under different temperature and humidity conditions, thereby regulating the release rate of N,N-diethyl-2-hydroxy-2-phenylacetamide.

[0090] Synthesis method: 5-bromo-2-hydroxyacetophenone and hydroxylamine hydrochloride are used as raw materials, and reacted in pyridine solvent under alkaline conditions. After the reaction is completed, the reaction solution is poured into ice water, and solids are precipitated. The crude product is filtered to obtain a crude product, and then recrystallized with a mixed solvent of ethyl acetate and petroleum ether to obtain pure 5-bromo-2-hydroxyacetophenone oxime.

[0091] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing a mixed solution for the mosquito repellent bracelet, 3 parts of 5-bromo-2-hydroxyacetophenone oxime were added. The other steps were the same as those in Example 1.

[0092] Comparative test: The mosquito repellent bracelet prepared in this embodiment is compared with the bracelet without the modifier added in Example 2. Under long-term outdoor light, the mosquito repellent effect of the bracelet in this embodiment can still reach 70% after 7 days of use, while the mosquito repellent effect of the bracelet in Example 2 is reduced to 50%.

[0093] Example 8

[0094] Modified organic compound: 3-Mercapto-5-methoxybenzoic acid butyl ester

[0095] Design principle: The thiol group reacts with the carbonyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to achieve loading. The methoxy group enhances the hydrophilicity of the molecule, making it more dispersed in the system. The ester group of the butyl benzoate part can be hydrolyzed under different environments to control the release of N,N-diethyl-2-hydroxy-2-phenylacetamide. The butyl group has a certain hydrophobicity and can combine with the polymer material of the bracelet through hydrophobic interaction to enhance adhesion.

[0096] Mechanism of action of the group: The thiol group reacts with the carbonyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form a stable chemical bond. The methoxy group improves the solubility of the molecule in water and makes it more evenly distributed during the preparation process.

[0097] Under chemical action, it slowly hydrolyzes and gradually releases N,N-diethyl-2-hydroxy-2-phenylacetamide. The butyl group interacts with the hydrophobic region of the bracelet material to improve the stability of the modified compound in the bracelet.

[0098] Synthesis method: 3-mercapto-5-methoxybenzoic acid and butanol are used as raw materials, and the esterification reaction is carried out by heating and refluxing in a toluene solvent under the catalysis of concentrated sulfuric acid. After the reaction is completed, the reaction solution is poured into a saturated sodium carbonate solution, separated, and the organic phase is taken, dried with anhydrous sodium sulfate, filtered, and then toluene is removed by reduced pressure distillation to obtain 3-mercapto-5-methoxybenzoic acid butyl ester.

[0099] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing the mixed solution of the mosquito repellent bracelet, 5 parts of 3-mercapto-5-methoxybenzoic acid butyl ester were added. The other steps were the same as those in Example 2.

[0100] Comparative test: The mosquito repellent bracelet prepared in this embodiment is compared with the common mosquito repellent bracelet on the market. Under different temperature environments (15°C-35°C), the mosquito repellent effect of the bracelet in this embodiment fluctuates less. After 6 days of use, the average mosquito repellent effect remains above 70%, while the mosquito repellent effect of the common mosquito repellent bracelet on the market fluctuates greatly, and the average mosquito repellent effect after 6 days is only 50%.

[0101] Example 9

[0102] Modified organic compound: 4-amino-3-chlorobenzoic acid isopentyl ester

[0103] Design principle: The amino group reacts with the carboxyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form an amide bond to achieve loading. The chlorine atom enhances the stability of the molecule and regulates the interaction with N,N-diethyl-2-hydroxy-2-phenylacetamide. The ester group of the isopentyl benzoate part can be hydrolyzed under different environments to control the release of N,N-diethyl-2-hydroxy-2-phenylacetamide. The isopentyl group has certain hydrophobicity and steric hindrance, and can better combine with the bracelet material.

[0104] Mechanism of group action: The amino group reacts with the carboxyl group of N,N-diethyl-2-hydroxy-2-phenylacetamide to form a stable connection. The chlorine atom affects the binding mode and stability of the molecule with N,N-diethyl-2-hydroxy-2-phenylacetamide through electronic effects and steric hindrance. The ester group hydrolyzes under different pH values ​​or under the action of microorganisms, gradually releasing N,N-diethyl-2-hydroxy-2-phenylacetamide. The isopentyl group interacts with the polymer material of the bracelet to enhance the adhesion of the modified compound in the bracelet.

[0105] Synthesis method: 4-amino-3-chlorobenzoic acid and isopentanol are used as raw materials, and the esterification reaction is carried out by heating and refluxing in a cyclohexane solvent under the catalysis of concentrated sulfuric acid. After the reaction is completed, the mixture is washed with a saturated sodium bicarbonate solution and water in turn, separated, and the organic phase is taken and dried with anhydrous sodium sulfate. After filtering, the cyclohexane is removed by reduced pressure distillation to obtain 4-amino-3-chlorobenzoic acid isopentanol.

[0106] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing the mixed solution of the mosquito repellent bracelet, 4 parts of 4-amino-3-chlorobenzoic acid isopentyl ester were added. The other steps were the same as those in Example 3.

[0107] Comparative test: The mosquito repellent bracelet prepared in this embodiment is compared with the same bracelet without adding the modifier. In a simulated daily wear friction environment, after the bracelet of this embodiment is used for 4 days, the residual amount of N,N-diethyl-2-hydroxy-2-phenylacetamide is 65% of the initial loading amount, while the residual amount of the bracelet without adding the modifier is only 45%.

[0108] Example 10

[0109] Modified organic compound: 2-Hydroxy-4-nitrobenzoylhydrazide

[0110] Design principle: The hydroxyl group forms hydrogen bonds with the hydroxyl group on the surface of the bracelet material to enhance adhesion. The hydrazide group forms hydrogen bonds or other weak interactions with N,N-diethyl-2-hydroxy-2-phenylacetamide to achieve loading. The nitro group has strong electron-withdrawing properties, which regulates the electron cloud distribution of the molecule, affects the interaction with N,N-diethyl-2-hydroxy-2-phenylacetamide and the adsorption performance in the bracelet, thereby controlling the release of N,N-diethyl-2-hydroxy-2-phenylacetamide.

[0111] Mechanism of group action: The hydroxyl group is tightly bound to the hydroxyl group of the bracelet material through hydrogen bonds. The hydrazide group is bound to N,N-diethyl-2-hydroxy-2-phenylacetamide through hydrogen bonds or van der Waals forces to stabilize the load. The nitro group changes the electron cloud around the molecule through the electron-withdrawing effect, making the binding of N,N-diethyl-2-hydroxy-2-phenylacetamide more stable. Under different environmental factors (such as temperature and humidity changes), the nitro group affects the conformational changes of the molecule, thereby regulating the release rate of N,N-diethyl-2-hydroxy-2-phenylacetamide.

[0112] Synthesis method: 2-hydroxy-4-nitrobenzoic acid is used as a raw material, and hydrazine is reacted in an ethanol solvent under heating and reflux conditions. After the reaction is completed, it is cooled, and solids are precipitated. The crude product is filtered to obtain a crude product, and then recrystallized with a mixed solvent of ethanol and water to obtain pure 2-hydroxy-4-nitrobenzoyl hydrazide.

[0113] Preparation of a mosquito repellent bracelet containing a modified sustained-release agent: In the step of preparing the mixed solution of the mosquito repellent bracelet, 3 parts of 2-hydroxy-4-nitrobenzoyl hydrazide are added. The other steps are the same as those in Example 1.

[0114] Comparative test: The mosquito repellent bracelet prepared in this embodiment is compared with the bracelet without the modifier added in Example 2. In an outdoor high humidity (70%) and sunlight environment, the mosquito repellent effect of the bracelet in this embodiment can still reach 75% after 6 days of use, while the mosquito repellent effect of the bracelet in Example 2 is reduced to 55%.

[0115] Embodiment 11

[0116] The structure, composition and properties of the material are confirmed through a variety of analytical techniques. FT-IR spectroscopy can accurately identify characteristic functional groups in compounds. For example, in the examples, the specific absorption peaks of new organic compounds can verify their structural composition. 1H NMR further determines the environment and number of hydrogen atoms in the molecule through chemical shift and peak area, and assists in clarifying the structure of the compound.

[0117] Elemental analysis gives the proportion of each element in a quantitative form to ensure that the synthetic product meets expectations. These technologies confirm each other and ensure from different angles that the newly synthesized modifiers and recycled materials have accurate chemical structures and synergistic effects, as shown in Table 1:

[0118] Table 1 Characterization and verification

[0119]

[0120]

[0121] The above implementation modes are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field should fall within the protection scope determined by the claims of the present invention.

Claims

1. A mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide, characterized in that: Calculated by weight, including: 3-10 parts of N,N-diethyl-2-hydroxy-2-phenylacetamide; 8-15 parts of a high molecular weight polymer carrier with sustained release function, wherein the carrier is polylactic acid-glycolic acid copolymer (PLGA); 2-6 parts of plasticizer, tributyl citrate; 1-4 parts of antioxidant, which is di-tert-butyl-p-cresol; 0.5-2 parts lavender essential oil; 0.1-1 parts of nano titanium dioxide.

2. The mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide according to claim 1, characterized in that: The high molecular polymer carrier with sustained release function has a molar ratio of lactic acid to glycolic acid of 75:25-50:50 and a molecular weight of 50,000-100,000.

3. The mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide according to claim 1, characterized in that: The particle size of the nano titanium dioxide is 20-50 nanometers.

4. A method for preparing a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide, characterized in that: The following steps are involved: Preparation of PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide: dissolving N,N-diethyl-2-hydroxy-2-phenylacetamide in dichloromethane, adding the dichloromethane solution of PLGA, and ultrasonic emulsification to form an oil phase; slowly dropping the oil phase into an aqueous solution containing polyvinyl alcohol (PVA), stirring at a high speed to volatilize the dichloromethane, and forming PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide; Prepare a mixed solution: add plasticizer tributyl citrate, antioxidant di-tert-butyl-p-cresol (BHT), fragrance lavender essential oil, and nano titanium dioxide into an appropriate amount of tetrahydrofuran (THF), stir evenly, and form a mixed solution; Preparation of mosquito repellent bracelet material: adding PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide to the above mixed solution, and then adding thermoplastic polyurethane elastomer (TPU) containing nanocellulose, stirring at 50-70° C. until completely dissolved to form a uniform solution; Molding: Pour the above solution into a customized bracelet mold, cool it naturally at room temperature to form it, or dry it at 40-60°C to form it, and after demolding, a mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide is obtained.

5. The method according to claim 4, characterized in that In the process of preparing PLGA microspheres loaded with N,N-diethyl-2-hydroxy-2-phenylacetamide, the particle size distribution and encapsulation efficiency of the microspheres were adjusted by changing the power and time of ultrasonic emulsification and the concentration of PVA.

6. The method according to claim 4, characterized in that In the molding step, when the hot pressing molding process is adopted, the pressure is controlled at 5-10 MPa, the temperature is 120-150° C., and the time is 5-10 minutes.

7. An application of the mosquito repellent bracelet according to any one of claims 1 to 3 in outdoor activities, characterized in that: The mosquito repellent bracelet is used in outdoor activities.

8. A mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide prepared by the method according to any one of claims 4 to 6, characterized in that: Its tensile strength reaches 10-15MPa, and its elongation at break is 300-500%. It can adapt to the wearing needs of different wrist sizes and is not easy to deform or damage during long-term use.

9. A mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide, characterized in that: On the basis of any one of claims 1 to 3, a modified organic compound is further added, and the modified organic compound is one or more of 3-amino-4-methoxyphenylacetic acid benzyl ester, 2-hydroxy-5-nitrobenzaldehyde semicarbazone, 4-chloro-3-methylbenzoic acid-2-methoxyethyl ester, 5-bromo-2-hydroxyacetophenone oxime, 3-mercapto-5-methoxybenzoic acid butyl ester, 4-amino-3-chlorobenzoic acid isopentyl ester, and 2-hydroxy-4-nitrobenzoic acid hydrazide.

10. A method for preparing the mosquito repellent bracelet containing N,N-diethyl-2-hydroxy-2-phenylacetamide according to claim 9, characterized in that: In the method steps of any one of claims 4 to 6, a corresponding weight portion of a modified organic compound is added in the step of preparing the mixed solution.